CULTURAL POLICY AND THE RISE OF MULTICULTURALISM STUDY OF FINE ARTS EXHIBITION IN THE 2000s, THE NATIONAL GALLERY OF INDONESIA - Dewi, Citra Smara (UI Scholars Hub, 2020)
This study focuses on the role of cultural policy in the rise of multiculturalism with a case study of the Indonesian Art Exhibition, Pameran Seni Rupa Nusantara (PSRN) 2000s, which was initiated by a cultural institution, the National Gallery of Indonesia (GNI). PSRN exhibition is one of the important programs of GNI because it gives space to the artists of the archipelago - not just Java and Bali - to present works of modern-contemporary art rooted in local wisdom. As a nation that has the characteristics of pluralism, the spirit of multiculturalism in art has become very significant, especially in the middle of the Disruption era which is